SURVEI PENGGUNAAN ALAT PELINDUNG DIRI (APD) PETUGAS KEBERSIHAN DI RUMAH SAKIT ISLAM KABUPATEN KARAWANG - Jumaedi, Jumaedi; Wendi Darmawan; Muhidin, Muhidin; Chaerani Tri Yuliana; Yazin Azhari (Journal of Innovation Research and Knowledge, 2024)
This study aims to evaluate the compliance level of Personal Protective Equipment (PPE) usage by cleaning staff at the Islamic Hospital of Karawang Regency and to identify the factors influencing it. The data shows that the compliance level of PPE usage at this hospital has reached 90%, in accordance with the national standards set by the Indonesian Ministry of Health. Despite this high compliance rate, challenges remain in maintaining and further improving adherence. Several strategies, such as continuous training, strict supervision, effective inventory management, and incentive provision, have proven effective in enhancing compliance. The study also found that increasing PPE compliance contributes to a 40% reduction in nosocomial infections, positively impacting patient safety, economic efficiency, and the quality of healthcare services. Therefore, a combination of structured interventions and strong managerial support is essential to maintaining high compliance levels and ensuring a safer hospital environment